New records of the diversity of Scleroderma spp. from Papua, Indonesia - SUPENI SUFAATI; SUHARNO SUHARNO; VERENA AGUSTINI; NUTTIKA SUWANNASAI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sufaati S, Suharno, Agustini V, Suwannasai N. 2023. New records of the diversity of Scleroderma spp. from Papua, Indonesia. Biodiversitas 24: 4269-4276. Papuan forest is one of the highest diversity tropical rainforests in the world. However, in some areas it is undergoing in process of land degradation. Reforestation using local plant inoculated with native mycorrhiza may have better results since they will be more adaptable. Mycorrhiza helps in plant nutrient uptake and ameliorates heavy metals in mining areas. Genus Scleroderma is a group of ectomycorrhiza that can be found at early stage of succession. However, to date there has been little study on its taxonomy. This study was conducted to construct the database on the diversity of Scleroderma spp. in Papua, Indonesia. Samples were collected from several areas in the provinces of Papua and West Papua from 2003 to 2022. Morphological characters and its habitat were observed. The results show, that 23 isolates had been documented. Molecular identification using ITS sequences was used to confirm the Scleroderma to the species level. The results found at least 3 species of Scleroderma, namely: Scleroderma suthepense, S. xanthochroum, and S. sinnamariense were identified based on morphological and molecular analysis, while S. citrinum was identified morphologically. This finding provides new data on the distribution of Sclerodermataceae in Papua. The results of this preliminary study are important for selecting native Scleroderma spp. for inoculation programs in degraded land.